Celastrol Attenuates RANKL-Induced Osteoclastogenesis in vitro and Reduces Titanium Particle-Induced Osteolysis and Ovariectomy-Induced Bone Loss in vivo - Qiang Xu; Guiping Chen; Guiping Chen; Huaen Xu; Guoming Xia; Meisong Zhu; Haibo Zhan; Bin Zhang; Min Dai; Hongxian Fan; Hongxian Fan; Xuqiang Liu (Frontiers Media S.A., 2021)
Excessive bone resorption by osteoclasts contributes significantly to osteoclast-related diseases such as periprosthetic osteolysis and osteoporosis. Osteolysis in a titanium particle-induced calvarial model and bone loss in an ovariectomized mice model occurred similarly to those in humans; thus, these models can be used to evaluate potential therapies for aseptic prosthetic loosening and osteoporosis. Celastrol, which is extracted from the seeds of the genus Tripterygium, has been thoroughly investigated for its anti-inflammatory and anti-cancer pharmacological effects. However, the mechanisms involving bone metabolism by which celastrol inhibits osteoclastogenesis are not yet fully understood. We demonstrated that celastrol inhibited the receptor activator of nuclear factor κB ligand-induced osteoclastogenesis and the bone resorptive function of osteoclasts in vitro by inhibiting the activation of transforming growth factor β-activated kinase 1-mediated NF-κB and mitogen-activated protein kinase signaling pathways and downregulating osteoclastogenesis marker-related genes. Furthermore, celastrol was also shown to be beneficial in both the titanium particle-induced osteolysis calvarial and the murine ovariectomy-induced bone loss. Collectively, our results suggested that celastrol is promising for the prevention of aseptic prosthetic loosening and osteoporosis in the treatment of osteolytic diseases induced by disrupted osteoclast formation and function.